2017
DOI: 10.1007/s10695-017-0379-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis of molecular mechanism underlying gray-to-red body color formation in red crucian carp (Carassius auratus, red var.)

Abstract: Red crucian carp (Carassius auratus red var.) is an ornamental fish with vivid red/orange color. It has been found that the adult body color of this strain forms a gray-to-red change. In this study, skin transcriptomes of red crucian carp are first obtained for three different stages of body color development, named by gray-color (GC), color-variation (CV), and red-color (RC) stages, respectively. From the skins of GC, CV, and RC, 103,229; 108,208; and 120,184 transcripts have been identified, respectively. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 46 publications
7
42
2
Order By: Relevance
“…Also, the lower expression levels of tyr and tyrp‐1 genes under prolonged light treatment, which was reflected by high RGB and pale pink colour of fish, suggest that the prolonged light possibly caused harmful effects on melanin production. Similar results were obtained in Carassius auratus whereby tyrp‐1 gene decreased as the colour changed from grey to red (Zhang et al, ). Moreover, the mutation of tyrp‐1 gene in D. rerio caused the death of some melanophores (Krauss, Geiger‐Rudolph, Koch, Nusslein‐Volhard, & Irion, ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Also, the lower expression levels of tyr and tyrp‐1 genes under prolonged light treatment, which was reflected by high RGB and pale pink colour of fish, suggest that the prolonged light possibly caused harmful effects on melanin production. Similar results were obtained in Carassius auratus whereby tyrp‐1 gene decreased as the colour changed from grey to red (Zhang et al, ). Moreover, the mutation of tyrp‐1 gene in D. rerio caused the death of some melanophores (Krauss, Geiger‐Rudolph, Koch, Nusslein‐Volhard, & Irion, ).…”
Section: Discussionsupporting
confidence: 80%
“…In this study, we found that artificial photoperiod manipulation affected the contents of tyrosinase and cysteine. Based on colour observation after the experiment, these results indicate that tyrosinase and cysteine determine the melanin content in fish as suggested by Schwahn, Xu, Herrin, Bales, and Medrano, () and Zhang et al (). Generally, the synthesis of pheomelanin is facilitated by cysteine, which induces red/yellow colour (Jiang et al, ; Watson et al, ; Zhu et al, ).…”
Section: Discussionsupporting
confidence: 76%
“…Zhu et al () conducted a transcriptome analylsis of three different coloured varieties red tilapia and found that several key DEGs were related to pigment synthesis, that is, tyr, tyrp1, silv, sox10, slc24a5, cbs and slc7a11. A study of skin transcriptomes for red crucian carp at different developmental stages identified a number of DEGs associated with the melanogenesis, tyrosine metabolism and pteridine metabolism (Zhang, Liu, Peng, et al, ; Zhang, Liu, Fu, et al, ). In another study, to further explore the genetic mechanisms underlying body colour formation in crucian carp, Zhang et al (Zhang, Liu, Peng, et al, ; Zhang, Liu, Fu, et al, ) performed skin transcriptome analysis of red crucian carp and white crucian carp and suggested that genes related to MAPK, Wnt, the cell cycle, endocytosis signalling pathways and variations in melanogenesis might be responsible for the colour variation in this species.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, we mainly focused on the cGMP‐PKG signalling pathway because it could affect pteridine metabolism. The yellow to reddish pteridine pigments of xanthophores are synthesized from guanosine triphosphate (GTP) through the pteridine synthesis pathway, and the GTP (which can be hydrolysed to form cGMP) is essential to signal transduction in second‐messenger mechanisms (Zhang, Liu, Fu, et al, ; Zhang, Liu, Peng, et al, ). Therefore, the DEGs involved in the cGMP‐PKG signalling pathway, including upregulated genes (ADCY2, KCNMB2, PLCB3 and PPP3CA) and downregulated genes (CAC1S, ATP1A2, ATP2A1, ATP2A2, MYLK3, MYLK4, PRKG1 and PRKG2) in Y, could likely become candidate genes for colour variation.…”
Section: Discussionmentioning
confidence: 99%
“…The crucian carp Carassius auratus is a member of the family Cyprinidae (Teleostei) [1]. It is one of the important fish species in aquaculture, which is distributed widely in both Europe and Asia [2,3].…”
Section: Introductionmentioning
confidence: 99%